Use of nutritional supplements amongst individuals exercising at gymnasiums - Junejo, Shizma; Shakoor, Shazia; Mustehsan, Zille Huma; Lateef, Mehreen; Iftikhar, Hamza; Rabbani, Sarah (Progress in Nutrition, 2021)
Background: Various surveys all over the world have elucidated the extent of use of nutritional supplements for enhanced exercise as well as athletic performance. The use of nutritional supplements is becoming increasingly popular amongst individuals exercising in gymnasiums. The popular uses of nutritional supplements by individuals exercising in gymnasiums include  improved performance, rapid weight loss and prevention of injury.Objective: To assess use of nutritional supplements amongst individuals exercising at various gymnasiums in Karachi and Islamabad. Methods: This descriptive, cross-sectional study included 300    participants.  The questionnaires included information related to socio-demographics, activity level at work, days in a week exercising at gymnasium, types of exercises at gymnasium , benefits  experienced after nutritional supplements use, weight, height, smoker or non-smoker, number of cigarettes smoked in a day by participants who were smokers and  the number of hours the participants slept in a day.   Informed consent was taken from all participants prior to participation in this study. Following attainment of consent, participants were provided with questionnaires. Results: In this study 324 (74.5%) participants were aware of nutritional supplements. Majority 108 (24.8%) reported improved performance. Whey protein emerged as the nutritional supplement being used by majority of participants in this study. Associations between use of nutritional supplements before and after exercise with reasons, frequency, types and benefits were significant with a p value of less than 0.05. Conclusion: Use of nutritional supplements by individuals exercising in gymnasium can be highly beneficial for improved performance and prevention of injury.